Between work and life: how Generation Z perceives increasing job demands and the expectation of constant availability - Kozová, Kristína; Navickas, Valentinas; Grenčíková, Adriana; Kosáková, Simona (Transformations In Business & Economics, 2026)
The main objective of the article was to examine the relationship between work demands and their impact on the personal and family life of Generation Z employees. The research was based on the theoretical frameworks of Work Connectivity Behavior After-hours (WCBA) and the Job Demands–Resources (JD-R) theory, which explain the “double-edged” nature of technological connectivity – as both a source of flexibility and a factor increasing psychological strain. The empirical part was conducted in 2025 on a sample of 67 Generation Z respondents through an online questionnaire evaluated using a 5-point Likert scale. Correlation analysis and multiple linear regression analysis were used to process the data. The results confirmed two out of the three proposed hypotheses. A moderately strong negative relationship was identified between the perceived impact of work on personal and family commitments and the perception of increasing work demands, suggesting that when employees already perceive work as a source of private life disruption, they tend to be less sensitive to further increases in demands. At the same time, a weak but statistically significant positive relationship was confirmed between the expectation of work availability outside working hours and the perception of increasing demands. Conversely, the relationship between the impact of work on personal commitments and the expectation of availability was not confirmed. The findings highlight the need for targeted organizational policies focused on managing boundaries between work and private life. It is recommended to strengthen the culture of the “right to disconnect,” promote psychological detachment, foster digital leadership, and implement measures to prevent burnout. Effective management of digital availability appears to be a key prerequisite for sustainable work performance, mental well-being, and long-term job satisfaction among Generation Z employees.